Strategies for use, treatment, management and final disposition of wastes in academic laboratories - Vladimir Gaviria González; Fredy Edimer Hoyos Velasco; John E. Candelo-Becerra (Universitas Ahmad Dahlan, 2020)
Laboratory higher education institutions can generate a wide range of wastes,many of which have hazardous characteristics. The uncontrolled accumulation of such wastes also has a significant impact on the environment, safety and health of the academic community. This work formulates strategies that allow the development of integrated solutions to mitigate the latent risk for the community at Institución Universitaria Colegio Mayor de Antioquia,Colombia, and its surroundings. Therefore, it is considered to quantify the generation of waste in the units of analysis of different experimental spacesand evaluate the factors involved in the implementation of strategies for diagnosis, waste recovery, treatment, and final disposition. Based on the diagnosis and characterization of wastes, alternatives are evaluated that help to prevent and, in other cases, mitigate the impacts that they can cause, in order to consolidate a protocol for waste management. Hazardous waste disposition strategies, treatment mechanisms and minimization strategies, such as microchemistry, precipitation recycling, encapsulation and immobilization methods, evaporation as well as solvent recovery, have been implemented.